2021
DOI: 10.1101/2021.05.13.21257152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct Mucoinflammatory Phenotype and the Immunomodulatory Long Noncoding Transcripts Associated with SARS-CoV-2 Airway Infection

Abstract: Respiratory epithelial cells are the primary target for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We investigated the 3D human airway tissue model to evaluate innate epithelial cell responses to SARS-CoV-2 infection. A SARS-CoV-2 clinical isolate productively infected the 3D-airway model with a time-dependent increase in viral load (VL) and concurrent upregulation of airway immunomodulatory factors (IL-6, ICAM-1, and SCGB1A1) and respiratory mucins (MUC5AC, MUC5B, MUC2, and MUC4), and diffe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Expressions of hundreds of lncRNAs including uncharacterized novel transcripts have been identified in SARS-CoV-2 infected cells [32][33][34][35], BALF from the COVID-19 patients [35,36], and PBMC from COVID-19 patients [36][37][38][39]). In most of the studies, reanalyses of expression data for lncRNA from published transcriptomic data, except in two studies [33,37] were carried out. Combining the all-published results, expression of 87 lncRNA was increased and 283 lncRNA was decreased only in one study.…”
Section: Altered Expression Of Lncrna In Sars-cov-2 Infected Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Expressions of hundreds of lncRNAs including uncharacterized novel transcripts have been identified in SARS-CoV-2 infected cells [32][33][34][35], BALF from the COVID-19 patients [35,36], and PBMC from COVID-19 patients [36][37][38][39]). In most of the studies, reanalyses of expression data for lncRNA from published transcriptomic data, except in two studies [33,37] were carried out. Combining the all-published results, expression of 87 lncRNA was increased and 283 lncRNA was decreased only in one study.…”
Section: Altered Expression Of Lncrna In Sars-cov-2 Infected Cellsmentioning
confidence: 99%
“…Analyzing PCG co-expressed with the lncRNA or identifying interacting partners of the lncRNA from various databases and enrichment analyses inferred the possible role of the deregulated lncRNA in the pathogenesis of COVID-19. Such studies revealed that increased expression of LASI (antisense strand to ICAM-1, not annotated in NCBI and Ensembl database), TOSL (TNFAIP3-opposite strand lncRNA, not annotated in NCBI and Ensembl database) and NEAT1 might be involved in immunomodulation [33]. Analyzing the PCGs that modulate the expression of genes by acting in cis or trans as evident from the correlation of lncRNA-PCG, it has been inferred that MALAT1 and NEAT1 possibly contributed to the inflammation developed in the SARS-CoV-2 infected cells [36].…”
Section: Possible Functional Role Of the Deregulated Lncrna In Viral ...mentioning
confidence: 99%
See 2 more Smart Citations
“…SARS-CoV-2, as an RNA virus, shifts cell metabolism from oxidative phosphorylation to glycolysis, which triggers excessive inflammatory responses and cytokine storms ( Mahrooz et al, 2021 ), indicating that cellular metabolism is closely linked to SARS-CoV-2 infection. LncRNA is differentially expressed in COVID-19-infected patients ( Devadoss et al, 2021 ; Taheri et al, 2021 ). Therefore, the speculation above may also occur in SARS-CoV-2 infection, giving us a great impetus to explore the relationship between LncRNA, glycolysis, and antiviral innate immunity.…”
Section: The Relationship Between Glycolysis Lncrna and Antiviral Innate Immunitymentioning
confidence: 99%